Yarkovsky Effect on the Orbital Dynamics of 1566 Icarus Asteroid - Niken Rara Galih Amithya Parastuti; Endang Soegiartini (Indonesian Journal of Physics, 2019)
The orbital dynamic of small objects is an n-body problem that can not be solve by analitically, it is needed to use numerical integration to find the solution instead. This work is about orbital dynamic of asteroid 1566 Icarus under Classical Newtonian gravitation and if thermal effect (Yarkovsky effect) is included. Yarkovsky Effect is a thermal radiation force resulted from time span of small rotating objects to receive heat from the Sun and then re-radiates it. The Yarkovsky Effect is working optimum for objects with diameter from 10 cm up to 10 km, and now is implemented to Asteroid 1566 Icarus with diameter 1.3 km which are member of Apollo and Earth crosser object. This Asteroid is called Earth crosser due to its orbit is crossing Earth’s orbit. With semi major axis a  1.078 au and eccentricity e  0.827, asteroid 1566 Icarus has perihelion distance q = 0.18674 au or less than semi major axis of Mercury. Due to that reason, Yarkovsky effect was considered to be applied on the orbital dynamics of asteroid 1566 Icarus. Due to sensitivity in input-data of numerical integration for n-body, one hundred simulation preliminary data were made as input in numerical integration process, therefore, 100 clones of Asteroid 1566 Icarus are gathered. Cloning process was conducted by using random number from Asteroid 1566 Icarus orbital elements at epoch 2456800.5 (23 May 2014) to standard deviation . The integration then later conducted within 105 years time span from the epoch. The result shown that the orbital dynamics of asteroid 1566 Icarus with Yarkovsky effect is still within the range of 100 clones of asteroid 1566 Icarus. Thereby, within 105 years, Yarkovsky effect does not change the orbital dynamic of asteroid 1566 Icarus globally, except for two phenomenon between close encounter with planet.